Pengaruh Pemberian Pembiayaan Koperasi Syariah Terhadap Pendapatan Pedagang Pasar Tradisional Simpang Limun Kota Medan - zein aranita (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2019)
This study aims to determine the effect of giving Sharia cooperative financing to the income of the traditional market trader Simpang lemonade Medan who is a financing member of BMT El Munawar Medan. In this study, the samples taken were 39 respondents. This study uses a quantitative research approach. The technique used in sampling is Saturated Sampling Technique. The types of data used in this study are primary data and secondary data. The technique of collecting data uses a questionnaire. The data analysis technique used in this study was descriptive of respondents, classical assumption test analysis, simple linear regression, and hypothesis testing.The results of the t test (partial) show that the t-count for the financing variable of the Islamic cooperative (X) is = 21,261 to the income of traditional market tradersa) amounting to = 2.026 this means that t count is 21.261 t table 2.026, the output also shows the value of financing of sharia cooperatives (X) is significant 0.044 0.05 then Ha is accepted. Islamic Cooperative Financing (X) affects the income of traditional market traders (Y).The R Square Test results show that the total percentage variation in the dependent variable explained by the independent variable is 0.924 or 92.4%. This means that the magnitude of the influence of independent variables (variable financing of Islamic cooperatives) on the dependent variable (income of traditional market traders) is 92.4%, while the remaining 7.6% is explained by other variables outside of this study.Keywords: Financing, Revenue, and Traders